Application of fundamental techniques and tools for the translation of legal,technical, personal and academic documents from English to Spanish and from Spanish to English - Urrutia Romero, Jeannette Alessandra
The present work encompasses the process followed by the students in order to achieve the necessary scores to pass the translation fundamentals course. At the beginning, the work reviews the basic concepts of translation and its importance. In addition, the report shows different technological translation resources, computerassisted translation tools (CAT tools) and the main translation techniques, learned during this course, that are implemented to accomplish good translation works that fit the needs of the text or documents translated. The report also compiles different documents in the fields where translation assistance is required, such as: technology; with operation manuals and car magazines; academic degrees and birth, death and marriage, among other legal certificates that often demand professional translation services; all of them part of the practices completed by the students throughout the course and translated from the source language to the target language (from English to Spanish and from Spanish to English). At last, conclusions and recommendations exhibit the expertise accomplished by the students after all the translation practice performed within the specialization.